Reliability and Utility of a Lumbopelvic-hip Complex Stability Assessment in Individuals with Patellofemoral Pain - Erika Zambarano; Neal Glaviano; Amanda Murray (Bowling Green State University, 2022)
OBJECTIVE: Lumbopelvic-hip complex (LPHC) stability is related to altered movement patterns that are present in individuals with PFP. Current studies measuring LPHC function in PFP primarily assess endurance and not stability. A test of isolated LPHC stability, the Seated Trunk Control Test (STCT) was recently developed and test-retest reliability for the STCT has been shown to be excellent in a healthy population. To improve the clinical usefulness of the STCT, we aimed to establish test-retest reliability for individuals with PFP. We hypothesized the STCT would show good-to-excellent reliability. We also compared STCT performance between healthy individuals and those with PFP. We hypothesized those with PFP would have lower TTE and greater NE. MAIN OUTCOME MEASURES: Performance was measured as time to first error (TTE) and number of errors (NE) averaged between test trials. Intraclass correlation coefficients (ICC) with 95% confidence intervals (CI) assessed test-retest reliability utilizing a two-way mixed-effects model with single rater (ICC[3,1]). The Mann-Whitney U Test compared performance measures between groups, p < 0.05.